Сathode design effect on gas breakdown and modes of burning of the glow discharge in nitrogen - Lisovskiy, V.A.; Osmayev, R.O.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2018)
This paper reports the breakdown curves and current-voltage characteristics we have measured for the discharge in the dc electric field. It has been found that almost all breakdown curves measured for cathodes of different design (cylindrical one, two stepped cathodes, conical, spherical and pin ones) practically coincide with the curve for the gap value of 5 mm between flat electrodes near to and to the right of the minimum, excluding the sections for conical and pin cathodes within the gas pressure range above 10 Torr. Left-hand branches of breakdown curves diverge somewhat but they still behave themselves as a family of close curves. At low gas pressure the discharge is burning only in the abnormal mode with the smallest current observed with the pin cathode whereas the largest current occurs with the spherical one. At large pressure the normal mode is observed in the broad current range with the spherical and step cathodes and it is almost not seen with the pin one.